Posted by **Sandra** on Monday, May 5, 2014 at 5:20pm.

Multiply: (K+3)/(4K-2)*(12K^2 + 2k – 4)

• 3(k+3)/(3k+2)

• 3(k+3)(2k-1)/2

• (x-5)(3x+2)

• (x-5)(12x+8)

How?

11

- ALGEBRA -
**Steve**, Monday, May 5, 2014 at 5:58pm
well, 12k^2+2k-4 = 2(3k+2)(2k-1)

so, we have

(k+3)/2(2k-1) * 2(3k+2)(2k-1)

now the 2(2k-1) cancels, leaving

(k+3)(3k+2)

No idea about the 11.

## Answer This Question

## Related Questions

- math - how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 ...
- Algebra (new one since I put "match" (bad speller) - I have a few match ...
- algebra--1 question - Multiply. (k+3)/(4k-2)*(12k^2+2k-4) a. 3(k+3)/3k+2 b. 3(k+...
- Algebra - ((k^2+6k+9)/(k^2+12k+27))×(k^2+9)/((k^2+12k+27)) express in lowest ...
- Algebra. Please check my answers - Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42...
- Algebra - 2(3x - 7) + 4 (3 x + 2) = 6 (5 x + 9 ) + 3 how will solve it? well you...
- Algebra - for bobpursley - Problem given: 14-4(2k+4) = -2(4-3k) 14-8k-16 = -8+...
- Math - The problem to solve is: (x+20)(x-12)(x+4)>0 but I can't figure out ...
- intro cal - the first 3 term of a geometric progression are k-4, 2k-4, 4k+4. ...
- algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

More Related Questions